Communicating in Hospital Emergency Departments - Slade, D (Springer, 2016)
This book was conceived in response to the increasing recognition of the central role of communication in effective healthcare delivery, particularly in high-stress contexts. Over a three-year period, the research team investigated communication between patients and clinicians in five representative emergency departments (EDs). The book describes the communicative complexity and intensity of work in the ED and identifies the features of successful patient-clinician interactions. Drawing on authentic examples of communication within the ED, the book provides comprehensive communication strategies for healthcare professionals that can be readily integrated into everyday practice.